Structure Engineering of Graphene Nanocages toward High‐Performance Microwave Absorption Applications. Issue 2 (1st November 2021) - Zhang, Can; Li, Xueai; Shi, Yuning; Wu, Hongjing; Shen, Youfei; Wang, Chunsheng; Guo, Wanchun; Tian, Kesong; Wang, Haiyan
Abstract: Engineering of hollow nanostructure, represented by the carbon nanocages, has shown tremendous potential in addressing the impedance mismatch of carbonaceous microwave absorbers (MAs). However, issues with limited electric energy loss capacity caused by their localized graphitization characteristic and the isolated 0D structural layout of these reported models still need to be settled. Herein, for the first time, a controllable structure of 3D interconnected framework assembled with graphene nanocages (3DIGCs) is constructed via a self‐sacrificing in‐situ growth. The elaborate air‐filled interconnected cavities impart desirable impedance matching to absorber and facilitate multi‐scattering of microwave; while the archipelago‐like continuous framework with a remarkable electrical conductivity (≈1265.8 S m −1 ) boosts their electric energy loss capacity by introducing resistance loss and a synergistic reinforcing effect from dipolar polarization and interfacial polarization, in which the loss behaviors are innovatively unraveled via numerical simulation technology explicitly, further highlighting the structural advantages of 3DIGCs. As a result, 3DIGC‐750 delivers a strong reflection loss of −51.10 dB and an effective bandwidth of 4.40 GHz at only 1.45 mm, outperforming the reported carbon nanocage MAs. This work hereby provides a deep insight into employing structure engineering to develop high‐performance graphene nanocage MAs. Abstract : Structure engineering is developed by constructing 3D interconnected graphene nanocages via a self‐sacrificing in situ growth toward high‐performance microwave absorption. The air‐filled cavities ameliorate the impedance matching, while the interconnected archipelago‐like framework guarantees strong resistance loss and a synergistic reinforcing loss from polarization relaxations. Numerical simulation is performed to reveal their electromagnetic energy loss behavior innovatively, further highlighting the structural advantages.